ARTIFICIAL INTELLIGENCE DALAM KESEHATAN MENTAL (INOVASI, ETIKA, DAN MASA DEPAN) - Salahudin Liputo (Elsia: Jurnal Psikologi Manusia, 2025)
Artificial Intelligence (AI) has emerged as a transformative force in various fields, including mental healthcare. This review explores the integration of AI into mental healthcare, outlining current trends, ethical considerations, and future directions in this dynamic field. The review includes recent studies, examples of AI applications, and ethical considerations in this field. Current trends highlight the transformative potential of AI, with applications such as early detection of mental health disorders, personalized treatment plans, and AI-driven virtual therapists. However, these advances are accompanied by ethical challenges related to privacy, bias mitigation, and preserving the human element in therapy. Future directions emphasize the need for a clear regulatory framework, transparent validation of AI models, and continued research and development efforts. While AI has the potential to revolutionize mental healthcare, its responsible and ethical implementation is crucial. By addressing current challenges and thoughtfully defining future directions, we can fully leverage AI's potential to improve the accessibility, effectiveness, and ethics of mental healthcare services, thereby benefiting individuals and communities.